KREDIT MACET PADA KOPERASI SENIMAN SANGGAR KEMBANG BANG BANJAR KEDISAN TEGALLALANG GIANYAR - Filla Harlita, Intiara; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015)
The research was based on the grounds that in the provision of credit, thecooperatives based on the principle of trust and kinship, but the fact still going ondisfluencies in loan repayment, then was appointed title Kredit Macet pada KoperasiSeniman Sanggar Kembang Bang Banjar Kedisan Tegallalang Gianyar, because thecooperatives is have some problems of bad loans. The purpose of this paper is todetermine the causes of bad loans and and settlement efforts. The method of thisresearch is empirical through The Case Approach and The Fact Approach. Inconclusion, the bad loans to cooperatives caused by the debtor and settled through anegotiation process.
Keywords: Cooperatives, Bad Loans, Resolutions effort